2015
DOI: 10.1016/j.ydbio.2015.02.007
|View full text |Cite
|
Sign up to set email alerts
|

The orphan GPCR, Gpr161, regulates the retinoic acid and canonical Wnt pathways during neurulation

Abstract: The vacuolated lens (vl) mouse mutation arose on the C3H/HeSnJ background and results in lethality, neural tube defects (NTDs) and cataracts. The vl phenotypes are due to a deletion/frameshift mutation in the orphan GPCR, Gpr161. A recent study using a null allele demonstrated that Gpr161 functions in primary cilia and represses the Shh pathway. We show the hypomorphic Gpr161(vl) allele does not severely affect the Shh pathway. To identify additional pathways regulated by Gpr161 during neurulation, we took adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 68 publications
1
35
1
Order By: Relevance
“…Similarly, ciliary GPCRs can activate different downstream pathways depending on the cellular context. Indeed, a recent study uncovered a role of Gpr161 in activating canonical Wnt signaling in addition to its known role in mediating Shh signaling [52]. …”
Section: Rationale Behind Ciliary Signalingmentioning
confidence: 99%
“…Similarly, ciliary GPCRs can activate different downstream pathways depending on the cellular context. Indeed, a recent study uncovered a role of Gpr161 in activating canonical Wnt signaling in addition to its known role in mediating Shh signaling [52]. …”
Section: Rationale Behind Ciliary Signalingmentioning
confidence: 99%
“…GPR161 is a G-protein coupled receptor (GPCR) that is involved in neural tube development and acts as a regulator of cell signalling pathways, including Shh signalling, PKA signalling, retinoic acid signalling and Wnt signalling 31,32 . This was a particularly interesting hit as it has recently become clear that GPCRs function at membranes other than the plasma membrane 33 , and previous work has suggested that a Golgi-resident GPCR regulates transport from the Golgi, although the specific GPCR involved remains unknown 34 .…”
Section: Discussionmentioning
confidence: 99%
“…These include mitogen-activated protein kinase (MAPK), phosphoinositide 3-kinase (PI3K)-AKT, Hippo, nuclear factor k light-chain enhancer of activated B cells (NF-kB), and mammalian target of rapamycin (mTOR) pathways (Boehlke et al 2010;Christensen et al 2012;Wann et al 2014;Hansen et al 2015;Umberger and Caspary 2015). In addition, primary cilia were proposed to play a critical role in coordinating the balanced regulation of WNT/b-catenin versus WNT/PCP ( planar cell polarity) pathways (Lienkamp et al 2012;Oh and Katsanis 2013;Veland et al 2013;Li et al 2015;Saito et al 2015), which extensively cross talk with SHH, TGF-b, RTK, MAPK, Hippo, and Notch signaling (Bernascone and Martin-Belmonte 2013;Zhang et al 2014;Borggrefe et al 2016;Zhang et al 2016).…”
Section: Overview Of Signaling In Primary Ciliamentioning
confidence: 99%